Robust performance evaluation of independent agents - Ashwin Kambhampati (Theoretical Economics, 2024)
A principal provides incentives for independent agents. The principal cannot observe the agents' actions, nor does she know the entire set of actions available to them. It is shown that an anti-informativeness principle holds: very generally, robustly optimal contracts must link the incentive pay of the agents. In symmetric and binary environments, they must exhibit joint performance evaluation - each agent's pay is increasing in the performance of the other.
Keywords: D81; D82; D86; 330; Moral hazard; robustness; teams